Sex-specific epigenetic gene activation profiles are differentially modulated in human placentas affected by intrauterine growth restriction. (June 2020) - Meister, Sarah; Kolben, Thomas; Beyer, Susanne; Hutter, Stefan; Hofmann, Simone; Kuhn, Christina; Messner, Julia; Mayr, Doris; Solano, Maria Emilia; Jegen, Magdalena; Obermeier, Viola; Mahner, Sven; et al.
Highlights: In the syncytiotrophoblast a significantly lower expression of the histone protein H3K4me was found in female IUGR placentas. In contrast to H3K4me3, the H3K9ac expression was downregulated in the decidua of male IUGR foetuses. Double immunofluorescence staining revealed extravillous trophoblast cells as H3K9ac expressing cell population in the decidua. Prednisolone could also lead to histone modification changes in BeWo cells in vitro in a dose dependent manner. Abstract: Background: The purpose of this study was to investigate the sex specific expression of histone protein modifications responsible for rapid gene expression in IUGR placentas. Patients and Methods: We screened for fetal sex-specific expression of the histone proteins H3K4me3 and H3K9ac in 23 IUGR and 40 control placentas via immunohistochemistry. The trophoblast-like cell line BeWo was used in order to analyze a potential effect of stimulation with prednisolone on H3K4me3 and H3K9ac in vitro. Calculating regression models with additional adjustment for potential confounders were used. Results: A significantly decreased level of H3K4me3 was detectable in female syncytiotrophoblasts, whereas H3K9ac was reduced predominantly in male extravillous throphoblast (EVT). No association to the gestational age existed. Conclusion: Our data showed a reduced expression of the histone proteins H3K4me3 (female) and H3K9ac (male) in IUGR, furthermore elevated cortisol levels may lead to a sex-specific down-regulation of histone proteins in IUGR placentas.